Preoperative Breast Magnetic Resonance Imaging and Contralateral Breast Cancer Occurrence Among Older Women With Breast Cancer - Wang, Shi-Yi (J Clin Oncol, 2016)
PURPOSE: Preoperative magnetic resonance imaging (MRI) detects occult contralateral breast cancers (CBCs) in women with breast cancer, but the impact of detection on long-term CBC events is unclear. We examined whether MRI use decreases the occurrence of CBCs and the detection of stages II to IV disease among women who develop a CBC. PATIENTS AND METHODS: Analyzing the SEER-Medicare database, we assessed overall, synchronous (< 6 months after primary cancer diagnosis), and subsequent (ie, metachronous) stage-specific CBC occurrences in women who were diagnosed with stages I and II breast cancer during 2004-2009 and who were observed through 2011. RESULTS: Among 38,971 women with breast cancer, 6,377 (16.4%) received preoperative MRI. After propensity score matching, and compared with women who did not undergo MRI, preoperative MRI use was significantly associated with a higher synchronous CBC detection rate (126.4 v 42.9 per 1,000 person-years, respectively; hazard ratio, 2.85; P < .001) but a lower subsequent CBC detection rate (3.3 v 4.5 per 1,000 person-years, respectively; hazard ratio, 0.68; P = .002). However, the 5-year cumulative incidence of CBC remained significantly higher among women undergoing MRI compared with those not undergoing MRI (7.2% v 4.0%, respectively; P < .001). The analyses of projected CBC events for 10,000 patients who receive MRI indicated that, after a 5-year follow-up, MRI use would detect an additional 192 in situ CBCs (95% CI, 125 to 279) and 120 stage I CBCs (95% CI, 62 to 193) but would not have a significant impact on stages II to IV CBC occurrences (∼ 6; 95% CI, −21 to 47). CONCLUSION: An increased synchronous CBC detection rate, attributable to MRI, was not offset by a decrease of subsequent CBC occurrence among older women with early-stage breast cancer, suggesting that preoperative MRI in women with breast cancer may lead to overdiagnosis.